THE STATE OF CHOLESTEROL LEVEL IN HYPERTENSION IN SADANANYA HEALTH CENTER - Irpan Ali Rahman; Endrian Mulyadi Justitia Waluyo; Shafira Aisyah Darmawan (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Hypertension is an increase in systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. The number of hypertension sufferers has increased each year, in 2015 it reached 19,552, in 2016 it reached 24,750 and in 2017 it reached 38,057. In 2017 there were 115 hypertensive patients recorded in the report book that checked their health at the Sadananya Health Center. One of the causes of the high incidence of hypertension is cholesterol caused by the consumption of inappropriate food. One of the laboratory examinations to support hypertension diagnosis is blood cholesterol examination which can show excess cholesterol which makes hypertension difficult to control. To know the description of total cholesterol levels in hypertensive patients at the Sadananya Health Center. Quantitative descriptive, the population in this study were people with hypertension at the Sadananya Health Center. Sampling with accidental sampling, as many as 30 respondents. The cholesterol examination method used is CHOD-PAP. The results showed that blood pressure in respondents all had high blood pressure, namely >140/90 mmHg (100%), a high cholesterol level of 24 respondents (80%), blood pressure 140-150 who had high cholesterol as many 13 respondents, blood pressure 160-170 who had high cholesterol as much 6 respondents, blood pressure >180 who had high cholesterol as much 5 respondents. This study concludes that hypertensive clients have more high total cholesterol levels, which is as much as 80% and normal 20%. More hypertensive patients have high total cholesterol levels, which are 80% and 20% normal.